Study protocol: the pragmatic, exploratory DELTA-JU trial of the group-based multimodal DELTA intervention for abstinent adolescents with substance use disorders living in youth welfare institutions - Kuitunen-Paul, Sören; Basedow, Lukas A.; Roessner, Veit; Golub, Yulia (Frontiers in Psychiatry, 2023)
Background: The DELTA intervention contains 16 weekly group sessions plus additional individual sessions and educational session for parents. It aims to reduce substance use and related problems such as substance use disorders (SUD) in adolescents. Recent results indicated positive effects in psychiatric outpatients. Conducting DELTA in youth welfare settings seems feasible, however, organizational and content adjustments such as smoking cessation elements should be added in order to reduce relapse risks and to prevent negative health consequences. Methods/design: The pre-registered DELTA-JU study (German Clinical Trials Register, DRKS00027913) is separated into three stages: In the adjustment stage during months 1-4, we will revise the DELTA manual based on semi-structured interviews (n = 10) with personnel from youth welfare institutions specialized in serving adolescents with SUD in the study region, analyzed with content analysis. In the sampling stage during months 5-22, participants qualifying for a SUD and willing to regularly participate in the 16 weekly DELTA-JU group sessions will be enrolled to either one of two arms (cluster randomization: immediate intervention, waitlist with subsequent intervention 16 weeks later). Adolescents will be assessed at baseline and follow-up (16 weeks after first group session) with an additional pre-assessment (16 weeks before intervention starts) for the waitlist group. Assessment procedures include questionnaires and clinical interviews amongst others. At the same time, institutional personnel will receive a one-day workshop on SUD-relevant topics based on the DELTA parental education group and on feedback from the qualitative interviews. Personnel will also be assessed twice with questionnaires. In the dissemination stage during months 23-24, final study evaluation results will be prepared and submitted for publication. Discussion: This study will create a setting-specific manual for vulnerable adolescents suffering from SUDs, and, in many cases, from co-occurring mental disorders. If shown to be effective, DELTA-JU can be disseminated within other institutions of youth welfare.